2015
DOI: 10.1177/1358863x15581448
|View full text |Cite
|
Sign up to set email alerts
|

Association of cardiovascular and biochemical risk factors with tibial artery calcification

Abstract: The cardiovascular risk factors that contribute to coronary calcification have been extensively studied while those related to tibial artery calcium are less well defined. We sought to determine the associations between cardiovascular risk factors and tibial artery calcification in a cohort of patients with and without significant peripheral atherosclerosis. A total of 222 patients without end-stage renal disease were identified in a prospectively maintained database containing tibial artery calcification (TAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Similar to our results, other studies reported correlations between risk factors and calcification, particularly between diabetes and chronic kidney disease 1416 . While latter was not known for our study population, association between diabetes and calcification burden was strongest among all risk factors.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to our results, other studies reported correlations between risk factors and calcification, particularly between diabetes and chronic kidney disease 1416 . While latter was not known for our study population, association between diabetes and calcification burden was strongest among all risk factors.…”
Section: Discussionsupporting
confidence: 92%
“…Calcification of the FPA is a relatively common condition 13 that is known to increase the risk of reconstruction failure, amputation, and mortality in patients with PAD 2 . While correlations between vascular calcification and age, chronic kidney disease, and type II diabetes mellitus were previously reported 1416 , the underlying mechanisms and prevalence of FPA calcification in general population are not clear due to lack of data from younger and healthier arteries and inability to longitudinally study this process in humans. Lack of consensus on the definition of calcification and classification of its burden 11 further complicates research in this relatively unexplored area.…”
Section: Discussionmentioning
confidence: 97%
“…Several reports have shown that vascular calcification is a common and clinically significant feature of advanced atherosclerosis, osteoporosis and chronic kidney disease, and it is highly correlated with cardiovascular morbidity and mortality (Deas et al 2015). Establishing screening programs for the detection of compounds that are active against this pathological process are therefore crucial.…”
Section: Discussionmentioning
confidence: 99%
“…57,58 Calcification in the lower extremity, particularly in the setting of diabetes mellitus or chronic kidney disease, 50,51,57,108 doubles cardiovascular mortality and quadruples the risk of amputation, 50,69 but the etiology of FPA calcification remains unclear and is an area of active research. 27,28,50,54,101,103 …”
Section: Femoropopliteal Artery Obstructive Diseasementioning
confidence: 99%